2014
DOI: 10.1044/2013_ajslp-13-0010
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Speaker Attributes in Adductor Spasmodic Dysphonia: Ratings From Unfamiliar Listeners

Abstract: Unfamiliar listeners judge speakers with ADSD more negatively than control speakers, with judgments extending beyond typical clinical measures. The results have implications for counseling and understanding the psychosocial effects of ADSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Some made inferences about the speakers that would not have been made by a trained clinician, such as the assumption that the distortions in samples of ADSD speech were attributable to a cognitive impairment. These results are consistent with previous studies that showed everyday listeners make judgments of ADSD speakers that go beyond voice and speech quality (Isetti et al, 2014).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Some made inferences about the speakers that would not have been made by a trained clinician, such as the assumption that the distortions in samples of ADSD speech were attributable to a cognitive impairment. These results are consistent with previous studies that showed everyday listeners make judgments of ADSD speakers that go beyond voice and speech quality (Isetti et al, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…Belief in a cognitive cause for vocal deviance is also consistent with reports of individuals with ADSD that people are prone to talk down to them (Baylor et al, 2005). These qualitative findings also agree with quantitative results obtained from everyday listeners using rating scales for ADSD speakers (Isetti et al, 2014;Silverman & Hummer, 1989), as well as listeners who judge speakers with other intelligibility difficulties (Klasner, Yorkston, & Lillvik, 2002).…”
Section: Judgments About Speakers With Adsdsupporting
confidence: 88%
See 2 more Smart Citations
“…This study highlights the sound and speech characteristics of SD that evoke negative and judgemental reactions from listeners. As a result, individuals with SD experience a social penalty [33]. This emphasises the need for a better understanding of the underlying basis of perceptual judgements of voice in everyday communication [32].…”
Section: A Qualitative Study [32] Of Expert and Everyday Listener's Pmentioning
confidence: 99%